First record of Chloridea (Heliothis) subflexa (Lepidoptera: Noctuidae: Heliothinae) on cape gooseberry (Physalis peruviana) in Brazil - Campos de Melo, Aniela Pilar (2018)
1 recurso en línea (páginas 267-272) : ilustraciones color.